Acute Sigmoid Sinus Compromise Following Skull Base Procedures: Is a “Laissez-Faire” Approach Best? - Arnone, Gregory D.; Kunigelis, Katherine E.; Gurau, Andrei; Coulter, Ian; Thompson, John; Youssef, A. Samy (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Venous sinus compromise (VSC) of the sigmoid sinus can manifest as either venous sinus thrombosis, stenosis, or a combination of the two. It may occur following retro and presigmoid craniotomy, even in the absence of overt intraoperative sinus injury. Currently, the optimal management of VSC in the perioperative period is not well established. We report our incidence and management of VSC following skull base surgery around the sigmoid sinus.Patients and Methods A retrospective chart review of all patients undergoing presigmoid, retrosigmoid, or combined approach by the senior author from 2014 to 2019 was performed.Main Outcome Measures Charts were reviewed for patient demographics, surgical details, details of venous sinus compromise, and patient outcomes. Statistical analyses were performed using R 3.6.0 (R Project).Results A 115 surgeries were found with a total of 13 cases of VSC (overall incidence of 11.3%). Nine cases exhibited thrombosis and four stenosis. There were no statistically significant differences between the groups with (group 1) or without (group 2) VSC. Operation on the side of the dominant sinus did not predispose to postoperative VSC. Five patients received antiplatelet medication in the perioperative period. There was no difference in outcomes in the group that did not receive antiplatelet medication versus those who did.Conclusion Acute iatrogenic sigmoid sinus compromise can be managed expectantly. We believe that the treatment for each instance of VSC must be individualized, considering the symptoms of the patient, rather than applying a universal algorithm.
Keywords: dural venous sinus thrombosis; cerebral venous sinus thrombosis; sigmoid sinus; skull base surgery; neurosurgery; retrosigmoid; translabyrinthine